Fitness cost of mcr-1-mediated polymyxin resistance in Klebsiella pneumoniae. (5th March 2018) - Nang, Sue C; Morris, Faye C; McDonald, Michael J; Han, Mei-Ling; Wang, Jiping; Strugnell, Richard A; Velkov, Tony; Li, Jian
Abstract: Objectives: The discovery of mobile colistin resistance mcr-1, a plasmid-borne polymyxin resistance gene, highlights the potential for widespread resistance to the last-line polymyxins. In the present study, we investigated the impact of mcr-1 acquisition on polymyxin resistance and biological fitness in Klebsiella pneumoniae . Methods: K. pneumoniae B5055 was used as the parental strain for the construction of strains carrying vector only (pBBR1MCS-5) and mcr-1 recombinant plasmids (p mcr-1 ). Plasmid stability was determined by serial passaging for 10 consecutive days in antibiotic-free LB broth, followed by patching on gentamicin-containing and antibiotic-free LB agar plates. Lipid A was analysed using LC–MS. The biological fitness was examined using an in vitro competition assay analysed with flow cytometry. The in vivo fitness cost of mcr-1 was evaluated in a neutropenic mouse thigh infection model. Results: Increased polymyxin resistance was observed following acquisition of mcr-1 in K. pneumoniae B5055. The modification of lipid A with phosphoethanolamine following mcr-1 addition was demonstrated by lipid A profiling. The plasmid stability assay revealed the instability of the plasmid after acquiring mcr-1 . Reduced in vitro biological fitness and in vivo growth were observed with the mcr-1 -carrying K. pneumoniae strain. Conclusions: Although mcr-1 confers a moderate level of polymyxin resistance, it is associated with a significant biological fitness cost in K. pneumoniae . This indicates that mcr-1 -mediated resistance in K. pneumoniae could be attenuated by limiting the usage of polymyxins.